1999
DOI: 10.1038/sj.bjc.6690676
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in sporadic colorectal cancer is not an independent prognostic factor

Abstract: Summary Hereditary non-polyposis colorectal cancer (HNPCC) is linked to an inherited defect in the DNA mismatch repair system. DNA from HNPCC tumours shows microsatellite instability (MSI). It has been reported that HNPCC patients have a better prognosis than patients with sporadic colorectal cancer. We examined whether the presence of MSI in a series of unselected colorectal tumours carries prognostic information. In a series of 181 unselected colorectal tumours, 22 tumours (12%) showed MSI. Survival analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
48
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 17 publications
9
48
1
1
Order By: Relevance
“…In general, cases of CRLM appear to maintain relatively low MSI rates when compared with corresponding primary tumours, which consistently maintain MSI rates of 15-20%. This difference has been indicated to be statistically significant in at least one matched study (10). The absence of data regarding the MSI status of primary tumours in the present study precludes a discussion regarding corresponding expression.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In general, cases of CRLM appear to maintain relatively low MSI rates when compared with corresponding primary tumours, which consistently maintain MSI rates of 15-20%. This difference has been indicated to be statistically significant in at least one matched study (10). The absence of data regarding the MSI status of primary tumours in the present study precludes a discussion regarding corresponding expression.…”
Section: Discussionmentioning
confidence: 49%
“…These parameters have significant limitations and are based on population data rather than being individualized for each patient. Recent attention has therefore focused on the relevance of molecular prognostic markers (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Data on the prognosis of MSI-H CRC are conflicting. Salahshor et al (1999) found an obvious trend towards a better outcome of their MSI-H collective, but this was not statistically significant. Feeley et al (1999) could not see any impact of microsatellite status on patients' survival at all, but the validity of this study is limited by the low number of MSI-H cases.…”
mentioning
confidence: 73%
“…Several studies have found no correlation between MSI and age in patients with colon carcinoma. 17,[27][28][29][30] However, most of those studies had a small sample sizes and may have lacked the power to detect statistically significant associations. hMLH1 expression loss spread over different age groups was not examined systematically in any of those studies.…”
Section: Hmlh1 Expression Loss Age and Gendermentioning
confidence: 99%